2019
DOI: 10.1111/nph.16234
|View full text |Cite
|
Sign up to set email alerts
|

A wheat transcription factor positively sets seed vigour by regulating the grain nitrate signal

Abstract: Summary Seed vigour and early establishment are important factors determining the yield of crops. A wheat nitrate‐inducible NAC transcription factor, TaNAC2, plays a critical role in promoting crop growth and nitrogen use efficiency (NUE), and now its role in seed vigour is revealed. A TaNAC2 regulated gene was identified that is a NRT2‐type nitrate transporter TaNRT2.5 with a key role in seed vigour. Overexpressing TaNAC2‐5A increases grain nitrate concentration and seed vigour by directly binding to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…Given the increasing number of NRT1/NPF (Buchner and Hawkesford, 2014) and NRT2 (in this study) genes recently identified in bread wheat and their functional verification (Li et al, 2020), more elements of the cross talk between ABA and nitrate acquisition and singling are likely to be uncovered in this important crop. In Arabidopsis, at least four nitrate transporters, including AtNPF4.6/NRT1.2/AIT1, were found to also function as ABA transporters (Kanno et al, 2012).…”
Section: Taanr1 and Tawabi5 Are Essential Components Shaping The Two-mentioning
confidence: 85%
See 1 more Smart Citation
“…Given the increasing number of NRT1/NPF (Buchner and Hawkesford, 2014) and NRT2 (in this study) genes recently identified in bread wheat and their functional verification (Li et al, 2020), more elements of the cross talk between ABA and nitrate acquisition and singling are likely to be uncovered in this important crop. In Arabidopsis, at least four nitrate transporters, including AtNPF4.6/NRT1.2/AIT1, were found to also function as ABA transporters (Kanno et al, 2012).…”
Section: Taanr1 and Tawabi5 Are Essential Components Shaping The Two-mentioning
confidence: 85%
“…Previously, due to the lack of wheat genome information, only fragments of NRT2/NAR2 genes were isolated (Zhao et al, 2004;Yin et al, 2007;Taulemesse et al, 2015). However, the recent release of wheat whole-genome sequences (IWGSC, 2014(IWGSC, , 2018 has opened a new era for genetic studies in bread wheat (Wang et al, 2015), giving an opportunity to deepen our understanding of the genetic basis that underpins wheat's capacity for NO 3 2 uptake (Wang et al, 2018a;Li et al, 2020).…”
mentioning
confidence: 99%
“…RNA concentration and purity was measured using Qubit (Thermo Fisher Scientific). Expression analysis of genes TaNRT1.1/NPF6.3 (Buchner et al, 2015), TaNR1 (Buchner et al, 2015), TaNiR1 (Buchner et al, 2015), TaGDH2 (Buchner et al, 2015), TaGS1 (Buchner et al, 2015), TaNADH-GoGAT (Li et al, 2020) and TaAMT1c et al, 2018), and TaEF1a from which the most stable to PSI-362 treatment was…”
Section: Rna Extraction and Rt-qpcrmentioning
confidence: 99%
“…In common wheat, NAC family TFs are involved in responses to abiotic and biotic stresses such as drought, salt tolerance and stripe rust (Feng et al ., 2014; Huang et al ., 2015; Mao et al ., 2014; Mao et al ., 2012; Tang et al ., 2012; Wang et al ., 2015; Xia et al ., 2010a,b; Xue et al ., 2006), as well as senescence, nutrient remobilization and grain‐filling duration (Alhabbar et al ., 2018b; Uauy et al ., 2006; Zhao et al ., 2015). Recently, a NAC TF TaNAC2‐5A was found promoting nitrogen use efficiency and seed vigour in common wheat (He et al ., 2015; Li et al ., 2020), and two NAC TFs ZmNAC128 and ZmNAC130 were identified as activators of zeins in maize (Zhang et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%